Mechanism of thermoviscoelasticity driven solid-liquid interface reducing friction for polymer alloy coating - Sheng Tan; Yimin Luo; Junhua Yang; Wei Wang; Xia Li; Baoguang Jia; Zhuangzhu Luo; Guangan Zhang (Friction)
Abstract High-temperature ablation is a common failure phenomenon that limits the service life of the transmission parts on heavy-duty machines used in heavy load, high temperature, high shock conditions due to in-sufficient supply of lubricating oil and grease. Traditional self-lubricating coatings prepared by inorganic, organic or organic-inorganic hybrid methods are prone to be oxidated at high temperatures to lose their friction reducing function, so that it is difficult to meet the engineering requirements of high-temperature lubrication. We design viscoelastic polymer coatings by a high-temperature self-lubricating and wear-resistant strategy. Polytetrafluoroethylene (PTFE, T m = 329 °C) and polyphenylene sulfide (PPS, T g = 84 °C, T m = 283 °C) are used to prepare a PTFE/PPS polymer alloy coating. As the temperature increases from 25 to 300 °C, the PTFE/PPS coating softens from glass state to viscoelastic state and viscous flow state, which is owing to the thermodynamic transformation characteristic of the PPS component. Additionally the friction coefficient (µ) decreased from 0.096 to 0.042 with the increasing of temperature from 25 to 300 °C. The mechanism of mechanical deformation and surface morphology evolution for the PTFE/PPS coating under the multi-field coupling action of temperature (T), temperature-centrifugal force (T-F ω ), temperature-centrifugal force-shearing force (T-F ω -F τ ) were investigated. The physical model of “thermoviscoelasticity driven solid-liquid interface reducing friction” is proposed to clarify the self-lubricating mechanism determined by the high-temperature viscoelastic properties of polymers. The high-temperature adjusts the viscosity (η) of the coating, increases interface slipping and intensifies shear deformation (τ), reducing the friction coefficient. The result is expected to provide a new idea for designing anti-ablation coatings served in high temperature friction and wear conditions.